Optimization of Business Sustainability: Break-Even Point and Margin of Safety Analysis in the "Aneka Rasa Puspita" Cracker Business Sector - Indarriyanti, Henni; Wahyudi, Arif; Masrunik, Endah (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Business sustainability is a fundamental prerequisite for ensuring long-term financial viability and mitigating the negative externalities of commercial operations. Consequently, this study was undertaken to analyze the optimization of business sustainability utilizing the Break-Even Point (BEP) and Margin of Safety (MOS) metrics within the Puspita assorted-flavor cracker enterprise, situated in Wonotirto District, Blitar Regency. The derived information serves as a crucial foundation for managerial decision-making, specifically in the domains of profit planning and sales control. The methodological approach employed was a qualitative descriptive design. Data collection involved direct observation, interviews, and documentation. The analytical focus centered on calculating the break-even point in both unit and monetary (rupiah) terms, alongside the computation of the Margin of Safety to establish the secure threshold for sales reduction before incurring financial losses. The research findings demonstrate that the "Aneka Rasa Puspita" cracker business is currently operating above its break-even point. This signifies that the enterprise successfully covers all fixed and variable costs and is generating a profit. Furthermore, the calculated Margin of Safety exhibits a relatively high value, which indicates that the business possesses a robust level of operational security against potential decreases in sales volume. These findings offer a significant contribution to operational and strategic decision-making for Micro, Small, and Medium Enterprise (MSME) stakeholders, particularly in formulating policies regarding selling prices, sales targets, and cost control